AD, Volume 16, n° 2, 1991 - Full Issue - journal system, (Africa Development, 1991)
Contents Structural Adjustment and De-industrialisation in Nigeria:1986-1988 Yusuf Bangura ............................ 5 Prospects for Small-scale Industries Development Under a Structural Adjustment Program: The Case of Nigeria A. W. Obi .................................... 33 Désindustrialisation et crise de société en Algérie Said Chikhi ................................. 57 Trente ans de critique du système soviétique (1960-1990) Samir Amin ................................ 73 Workers in Nigeria's Social Development Experience: A Critique of Current Mythologies Jimi O. Adesina .......................... 95 Book Reviews The Urban African Worker and the Crisis of Apartheid Fassil Demissie .............................. 121 Prospects for Disengagement and Development in Southern Africa Mthuli Z. Neube ............................126 Publications Received .....................129